2013
DOI: 10.1159/000354443
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ecto-5´-Nucleotidase by Docosahexaenoic Acid in Human Endothelial Cells

Abstract: Background/Aims: Modulation of extracellular adenine nucleotide and adenosine concentrations is one potential mechanism by which docosahexaenoic acid (DHA) may exert beneficial effects in critically ill patients. This study assessed DHA effects on extracellular adenine purines. Methods: Experiments used human pulmonary endothelial cells (HPMEC) and umbilical vein endothelial cells (HUVEC) treated with DHA (48 h). mRNA level (real-time PCR), expression (western blot, flow cytometry) and activities (hydrolysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Thus, it appears that eNOS activity in presence of DHA is rather augmented via enzyme phosphorylation than by calcium stimulation. In conjunction with a previous study in which we reported enhanced ATP and ADP release from endothelial cells by DHA treatment [12], multiple effects of this omega-3-fatty acid may interact stimulating endothelial cell ATP release, which via autocrine P2Y receptor activation stimulates membrane calcium influx and simultaneously changes eNOS phosphorylation in a manner predictive of enhancing nitric oxide production. Here, a separate effect of DHA also resulting in ser1177 phosphorylation may augment ATP dependent stimulation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, it appears that eNOS activity in presence of DHA is rather augmented via enzyme phosphorylation than by calcium stimulation. In conjunction with a previous study in which we reported enhanced ATP and ADP release from endothelial cells by DHA treatment [12], multiple effects of this omega-3-fatty acid may interact stimulating endothelial cell ATP release, which via autocrine P2Y receptor activation stimulates membrane calcium influx and simultaneously changes eNOS phosphorylation in a manner predictive of enhancing nitric oxide production. Here, a separate effect of DHA also resulting in ser1177 phosphorylation may augment ATP dependent stimulation.…”
Section: Discussionsupporting
confidence: 70%
“…Once released, extracellular ATP enhances in an autocrine manner the endothelial cytosolic calcium and may subsequently increase endothelial cell nitric oxide production. As shown before, release and extracellular metabolism of ATP in endothelial cells are modulated by DHA resulting in an enhanced extracellular ATP concentration [12]. Thus, hypothetically a causal link may exist between the modulation of membrane lipid composition by DHA, extracellular ATP, endothelial cell calcium regulation and the generation of nitric oxide.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, some other studies have also reported that Wnt pathway [68], polyunsaturated fatty acid (PUFA) [69], and intracellular cAMP are also involved in regulation of CD73 expression [70]. Taken together, these results demonstrate that expression levels of CD73 are regulated by various factors via different mechanisms.…”
Section: Regulation Of Cd73 Expression In Cancermentioning
confidence: 60%
“…In this study, we noticed that DHA down-regulated the expression of CD39 and CD73 in two BC cells and their derived exosomes under hypoxic and normoxic conditions. Thom et al reported that CD39 activity was weaken after treatment with DHA in endothelial cells [ 32 ]. Their observations about expression of CD73 was increased in protein level but in mRNA level didn’t change after treatment with DHA [ 32 ].…”
Section: Discussionmentioning
confidence: 99%